COSO’s Enterprise Risk Management Framework in Agriculture Startup to Support the Achievement of SDGs Pillars - Ita Febrianti; Novita Novita (Universitas Airlangga, 2021)
COSO’s Enterprise Risk Management (ERM) is considered to increase the added value of the firm. This study's primary purpose is to discuss the implementation of the COSO’s ERM framework on agricultural startup in supporting the achievement of the SDGs pillars. Data collection methods used are questionnaires. This research uses qualitative and quantitative analysis using the Smart PLS application. It aims to determine the effect of implementation of COSO’s ERM as an added value to agricultural startup as a goal to support the achievement of SDGs pillars. Overall, the implementation of COSO’s ERM at the startup of Sayurbox has a significant effect in supporting the achievement of the economic, social and environmental SDGs pillars.